2020
DOI: 10.1029/2020jd032382
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Insolation and Soil Moisture on the Seasonality of Interactions Between the Madden‐Julian Oscillation and Maritime Continent

Abstract: This study investigates the seasonality of the interaction of the Madden‐Julian Oscillation (MJO) with the Maritime Continent (MC). Beside their seasonal east‐west migration with the monsoons, observations show that the MJO amplitude and precipitation over the MC islands exhibit semiannual variability, with apparent strengthening of MJO signal during March and September, when solar insolation is strongest over the MC region. Furthermore, during the high‐insolation months, soil moisture shows wetter conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…However, considering several MJO events that passed eastward from the northern part of the MC region into the Pacific Ocean, follow-up studies are still needed. The impacts of interannual variabilities of the ENSO, the Australian monsoon, and solar insolation in the MC region on the eastward propagation of MJO events have been revealed in previous studies (Hagos et al, 2019(Hagos et al, , 2020Hu, Chen, et al, 2022;Kang et al, 2022;Kim et al, 2017), but the results above suggest that the occurrences of the MJO_SC and MJO_N events are not entirely determined by these interannual variability factors in the background. In addition, previous studies have demonstrated the possible effects of oceanic eddies (Hu et al, 2021;Wen et al, 2020), oceanic fronts (Bai et al, 2019;Chen et al, 2019Chen et al, , 2020; Guan…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…However, considering several MJO events that passed eastward from the northern part of the MC region into the Pacific Ocean, follow-up studies are still needed. The impacts of interannual variabilities of the ENSO, the Australian monsoon, and solar insolation in the MC region on the eastward propagation of MJO events have been revealed in previous studies (Hagos et al, 2019(Hagos et al, , 2020Hu, Chen, et al, 2022;Kang et al, 2022;Kim et al, 2017), but the results above suggest that the occurrences of the MJO_SC and MJO_N events are not entirely determined by these interannual variability factors in the background. In addition, previous studies have demonstrated the possible effects of oceanic eddies (Hu et al, 2021;Wen et al, 2020), oceanic fronts (Bai et al, 2019;Chen et al, 2019Chen et al, , 2020; Guan…”
Section: Discussionmentioning
confidence: 67%
“…In the third and fourth sections, we will further investigate the differences in the accompanying climate effects and possible influencing mechanisms of oceanic processes. Furthermore, previous studies noted the impacts of interannual variability such as ENSO (Hagos et al, 2019;Hu, Wang, et al, 2022), Australian monsoon (Hagos et al, 2019;Kang et al, 2022;Kim et al, 2017), winter surface solar radiation in the MC region (Hagos et al, 2020) on the eastward propagation of MJO events during boreal winter. To remove the influence of interannual variability mentioned above, the anomalies are calculated by subtracting their annual winter average in the following sections.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…In a complementary approach using physics‐based models of various degrees of complexity, environmental conditions such as SSTs, upper‐level wind, or insolation etc. (e.g., Back et al., 2020; Hagos et al., 2020) are modified to determine the impact of the phenomenon of interest on a case study basis. Such an approach assumes the model adequately represents MJO propagation and its relationship to the background state.…”
Section: Introductionmentioning
confidence: 99%